Pola Komunikasi Organisasi Dalam Pengembangan Program Studi Filsafat Hindu STAH Negeri Mpu Kuturan Singaraja - I Putu Ariyasa Darmawan; I Made Gami Sandi Untara; Ni Wayan Juli Artiningsih (Jayapangus Press, 2021)
The STAH Negeri Mpu Kuturan Singaraja Hindu Philosophy Study Program is a new study program with minimal interest in prospective new students. Minimal in quantity, but the organization in the study program is currently complete, both lecturers, employees, and students. The minimum number of lecturers and students requires a form of communication that functions to unite study programs and minimize misunderstandings in interpreting orders or information. This research is a qualitative research with a phenomenological approach. Sources of data in this study were obtained by direct interviews and using several data sources that are helpful in analyzing such as books on communication. Data collection was carried out by observation, interviews with purposive sampling method, literature study, and documentation. The pattern of organizational communication in the Hindu Philosophy Study Program uses more top-down communication patterns, and bottom-up communication. The organizational communication function in the Hindu Philosophy study program STAHN Mpu Kuturan Singaraja is Informative Communication by using WhatsApp group chat Hindu Philosophy Study Programs to help lecturers and employees work on the Tri Dharma of Higher Education to be more focused, Regulatory Communication, namely the delivery of messages related to regulations in carry out the duties of the people who control the message of the organization, Persuasive Communication, namely changing attitudes and behavior as well as beliefs of a person, Integrative Communication functions and is useful for integrating all messages or information and communications that have been given by the leadership of the organization to members of the organization.